Experience Design for Reporting Human Trafficking - Lisa Mercer (Diseña, 2018)
The ethnographic research study titled Operation Compass is focused on the development of design-led interventions to combat human trafficking. Phase one was focused on the question, how could a modified form of technology enable truck drivers to report suspected instances of human trafficking at a higher rate? The collection of primary research was guided by grounded theory with the goal of developing a theory from social patterns to explain why truck drivers were not reporting suspected cases of human trafficking. The study identified three key factors: their fear of safety, the necessity for timely delivery of cargo, and the lack of understanding on how to identify human trafficking. Since these had previously stopped truck drivers from reporting suspected cases of human trafficking, our design goal was to create a reporting process that mitigated these concerns to the point that they could be overcome. That is, reporting had to be anonymous, convenient, safe, integrated into the technology truck drivers prefer to use, ease of use to report a suspected case of human trafficking, and the ability to recognize human trafficking. The first five could be addressed with the Operation Compass smartphone mobile application; the last required an education campaign.